Home Ownership and Home Equity Promote Entrepreneurial Activity - Wolter Hassink; Matteo Millone; Remco Mocking; Benedikt Vogt (Institute of Labor Economics (IZA), 2021)
This paper studies the effects of private real estate collateral on entrepreneurial lending and entrepreneurial activity in the Netherlands. The residential collateral channel is especially relevant for sole-proprietors who own a business with unlimited liability. We used administrative data on outstanding bank credit based on all Dutch sole-proprietorships in the 2007-2013 period. Our results indicate that, during a severe economic crisis, home-owning entrepreneurs are affected less severely than renting entrepreneurs. Home ownership improved access to credit at the extensive and intensive margin, and it reduced the probability of exit. Positive home equity is the driving force behind this effect, as entrepreneurs with negative home equity are not treated significantly differently from renters.
Keywords: G23; L26; R2; R31; 330; collateral lending channel; house price shocks; negative home equity; entrepreneurial lending